Evaluation of bioactivities of the bacterial strain Bacillus velezensis B26 - Aadarsh Ghurye, Shikar Joshi, Nikita Mahadev Pednekar, Nandini B. K. Shetty, Akshit V. Jain, Rakesh Rahangdale, Raghu Chandrashekhar, Subrahmanyam Volety Mallikarjuna, Kiran Kumar Kolathur (Journal of Applied Pharmaceutical Science, 2025)
Bacillus species are widely recognized as effective biocontrol agents utilized for suppressing plant pathogens. These species isolated from diverse habitats exhibit antifungal activity against several plant pathogens. Although complete genome sequences of several Bacillus species have been reported, exploration of the bioactivities of the Bacillus velezensis strains remains limited. In this study, we aimed to assess the bioactivities exhibited by the bacterial strain B. velezensis B26. Through our screening process, we identified B. velezensis B26 as a producer of chondroitinase enzyme, additionally demonstrating chitinase, glucanase, amylase, and gelatinase activities. Significantly, we unveil the potent antifungal capabilities of the B. velezensis B26 against opportunistic fungal pathogen Candida albicans and emerging fungal pathogen Saccharomyces cerevisiae.
Keywords: Glycosaminoglycans, chondroitin sulphate proteoglycans, chondroitinase, chitinase, glucanase